Sistem Perabot Modular: Meja Belajar - Amirul Haziq Sani; Haris Farhan Mohd Zulkafli; Mohamad Alifhaikal Arbain; Muhammad Azri Othman; Azizul Qayyum Basri (Multidisciplinary Applied Research and Innovation, 2024)
As students, we require a comfortable study space because it is one of the elements that can greatly affect the standard of instruction. However, the design of the rooms (2 large and 2 small rooms) and the identical size and quantity of furniture in each make them comfortable. Additionally, the number of students in each room is the same and is not dependent on the size of the room. This makes it difficult and disruptive to do any work or engage in any movement or daily activities in a room that is small in size and has the same large furniture. Because the wardrobe and bed are fixed sizes (standard), we suggest building a study table using a modular design to solve this issue. This furniture was developed for dorm room use by students to ensure comfort while studying and is only used internally. This product's frame is made of mild steel, which is simple to cut and shape, and is made more streamlined by having plywood cover the back and sides of the frame. To create a desk that took up less space, we created an adjustable English L and tied it with plywood. This idea was also used to create a laptop compartment that could be adjusted. According to our analysis, the desk can support up to 15 kg without tipping over or bending, while the adjustable laptop space can support up to 20 kg. According to the tests that have been conducted, the goal has been met in some cases. It is hoped that the system, structure, and general design of this product can be fixed.